THE ANALYSIS OF THE DISTRIBUTION AND RECIPIENTS OF RASKIN RICE ON THE NUMBER OF POOR PEOPLE IN INDONESIA - Ida Fitriyani; Devi Andriyani (Journal of Malikussaleh Public Economics, 2020)
This study aims to determine the analysis of the distribution and recipient of Raskin rice on the number of poor people in Indonesia during 2006-2017. This study uses time-series data from 2006 to 2017 obtained from the Indonesian Bulog and BPS Indonesia websites. The data are then analyzed using multiple linear regression analysis. The results show that the distribution and recipient of Raskin rice have a significant effect on the number of poor people in Indonesia during 2006-2017. Simultaneously, the distribution and recipient of Raskin rice have a significant and simultaneous influence on the number of poor people in Indonesia during 2006-2017. Keywords: The amount of rice distribution to the poor, rice recipients, the number of poor people.